Quality-Aware Tax Incentives for Charitable Contributions - Zachary Halberstam; James R. Hines (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper characterizes efficient tax subsidies for charitable contributions, and considers the properties of potential reforms. Contributions are underprovided in the absence of subsidies, and are misdirected if subsidies fail to account for all of the costs that donors incur. It is costly for prospective donors to identify high-quality giving opportunities, so there will be too few of these contributions if all giving receives the same tax treatment. A more efficient alternative is to offer generous tax subsidies that are partially or entirely recouped if recipient organizations subsequently experience precipitous contribution declines.
Keywords: H21; H41; L31; 330; Philanthropie; Fundraising; Steuervergünstigung; Theorie; USA